2007
DOI: 10.1254/jphs.fp0070534
|View full text |Cite
|
Sign up to set email alerts
|

Tranilast Suppresses the Disease Development of the Adjuvant- and Streptococcal Cell Wall-Induced Arthritis in Rats

Abstract: Abstract. This study explores the effects of the anti-allergic and anti-fibrotic agent tranilast on adjuvant-and streptococcal cell wall-induced arthritis in rats, animal models of rheumatoid arthritis in humans. Tranilast (150 or 300 mg / kg, twice daily) or vehicle only was administered orally to the two arthritis models, from 17 days before sensitization. As a comparative control, methotrexate (0.1 mg / kg, once daily) was given to another group. Tranilast suppressed the increase in foot volumes, paw thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…14,52) In this study, paw edema of the right hind feet of AA rats treated with the TL micro gel ointment was significantly decreased (Table 4, Fig. 8).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…14,52) In this study, paw edema of the right hind feet of AA rats treated with the TL micro gel ointment was significantly decreased (Table 4, Fig. 8).…”
Section: Discussionsupporting
confidence: 50%
“…13) Recently, it was reported that TL suppresses the development of RA in multiple models, and TL is expected to become a novel therapeutic agent for human RA. 14) Despite its positive pharmacological effects on inflammatory diseases, TL exhibits poor dissolution behavior and poor solubility (14.5 µg/mL in water), particularly under acidic conditions (0.7 µg/mL in buffer solution of pH 1.2), 15) so that the daily dose of TL must be relatively high (300 mg/d). Therefore, the oral administration of TL is often limited due to systemic side effects that include liver dysfunction, abdominal discomfort, skin rash, and allergic cystitis.…”
mentioning
confidence: 99%
“…Disease suppression was seen both in clinical parameters and histological findings across the whole pathology of arthritis. One of the proposed targets of MTX immune suppression is T cells [10]. As the pathology of SKG mice is dependent on autoreactive T cells presumably by genetic alteration [15], it is reasonable to hypothesize Marked bone erosion and synovial cell hyperplasia can be seen in B, and severe inflammatory cell infiltration can be seen in B1 for the mice in Group 2 (boxed area in B is enlarged as B1).…”
Section: Discussionmentioning
confidence: 99%
“…The H&E-stained preparations were microscopically observed focusing on the distal tibia-talocrural joint. The scoring methods were based on previous reports [10]. Briefly, the sum of a 4-point scoring system (0, no significant changes, 1, mild, 2, moderate, 3, marked) was considered as the histopathological score of each section, and the average score of each group was compared for bone erosion, new bone formation, pannus formation, cartilage destruction, synovial cell hyperplasia, inflammatory cell infiltration, circumarticular fibrosis and edema.…”
Section: Animalsmentioning
confidence: 99%
“…In arthritis research, the most common model systems are rodents like rats or mice. 1,2 Using animal models offer advantages like the possibility to observe systemic physiological effects by pharmaceutical agents. However, animal models also possess disadvantages.…”
Section: Introductionmentioning
confidence: 99%